Chronic impairment of ERK signaling in glutamatergic neurons of the forebrain does not affect spatial memory retention and LTP in the same manner as acute blockade of the ERK pathway. Issue 12 (7th September 2017) - Vithayathil, Joseph; Pucilowska, Joanna; Friel, David; Landreth, Gary E.
Abstract: The ERK/MAPK signaling pathway has been extensively studied in the context of learning and memory. Defects in this pathway underlie genetic diseases associated with intellectual disability, including impaired learning and memory. Numerous studies have investigated the impact of acute ERK/MAPK inhibition on long‐term potentiation and spatial memory. However, genetic knockouts of the ERKs have not been utilized to determine whether developmental perturbations of ERK/MAPK signaling affect LTP and memory formation in postnatal life. In this study, two different ERK2 conditional knockout mice were generated that restrict loss of ERK2 to excitatory neurons in the forebrain, but at different time‐points (embryonically and post‐natally). We found that embryonic loss of ERK2 had minimal effect on spatial memory retention and novel object recognition, while loss of ERK2 post‐natally had more pronounced effects in these behaviors. Loss of ERK2 in both models showed intact LTP compared to control animals, while loss of both ERK1 and ERK2 impaired late phase LTP. These findings indicate that ERK2 is not necessary for LTP and spatial memory retention and provide new insights into the functional deficits associated with the chronic impairment of ERK signaling.